Cardiac Metastases of Neuroendocrine Tumors Treated With 177Lu DOTATATE Peptide Receptor Radionuclide Therapy or 131I-MIBG Therapy. (December 2015) - Makis, William; McCann, Karey; Bryanton, Mark; McEwan, Alexander J.B.
Abstract : Abstract: Neuroendocrine tumors have a propensity to metastasize to the heart, although the reason for this remains unknown. A review of 251 neuroendocrine tumor patients treated with 177 Lu DOTATATE peptide receptor radionuclide therapy or 131 I-MIBG therapy at our institution since 2003 revealed 2 patients with cardiac metastases (incidence, 0.8%), one treated with 177 Lu DOTATATE and one with 131 I-MIBG. We present the imaging findings of these 2 patients, as well as their management and responses to therapy.